Serum Lipid Levels and Treatment Outcomes in Women Undergoing Assisted Reproduction: A Retrospective Cohort Study - Cai, Wang-Yu; Luo, Xi; Chen, Erxidi; Lv, Houyi; Fu, Kaiyou; Wu, Xiao-Ke; Xu, Jian (Frontiers in Endocrinology, 2021)
Objective To evaluate associations between serum lipid levels and treatment outcomes in women undergoing assisted reproduction. Materials and Methods The study included 2011 women who underwent in vitro fertilization/intracytoplasmic sperm injection with fresh embryo transfer. Serum lipid evaluation included total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TG). Ovarian stimulation outcomes included endometrial thickness and the number of oocytes retrieved, and reproductive outcomes included live birth, clinical pregnancy, and miscarriage. Results Higher HDL-C quartiles were associated with more oocytes retrieved. Lower TC (quartile 1 odds ratio [OR] 1.59 [1.21–2.08], quartile 3 OR 1.36 [1.04–1.77]), LDL-C (quartile 1 OR 1.41 [1.07–1.86]), and TG (quartile 2 OR 1.39 [1.06–1.84]) were independently associated with clinical pregnancy after adjusting for potential confounders. Lower LDL-C (quartile 1 OR 2.22 [1.58–3.13], quartile 2 OR 1.78 [1.27–2.50], quartile 3 OR 1.51 [1.07–2.13]), TC (quartile 1 OR 1.39 [1.00–1.93]), TG (quartile 1 OR 1.44 [1.03–2.03], quartile 2 OR 1.46 [1.04–2.04], quartile 3 OR 1.44 [1.04–1.99]), and higher HDL-C (quartile 2 OR 0.71 [0.51–0.99]) were independently associated with live birth. Higher LDL-C (quartile 1 OR 0.44 [0.30–0.66], quartile 2 OR 0.49 [0.33–0.73], quartile 3 OR 0.63 [0.43–0.94]) and lower HDL-C (quartile 1 OR 1.60 [1.07–2.39]) were independently associated with miscarriage. Conclusions Serum lipid levels were associated with treatment outcomes in women undergoing assisted reproduction.